ANALYSIS OF SUDAN'S POST-REFORMATION CONFLICT 2019: SUDAN ARMED FORCES (SAF) VS RAPID SUPPORT FORCES (RSF) - Nujuliyani, Shelvy; Tirto, Djayeng; Azhari, Yulian; Widodo, Pujo; Patmi, Sri (Natapraja, 2023)
This paper discusses the analysis of the post-reform 2019 Sudanese conflict between the Sudanese military or Sudan Armed Forces (SAF) against Sudanese paramilitaries or Rapid Support Forces (RSF). This research uses qualitative research methods through a juridical study approach to international humanitarian law. This law is a set of rules governing the law of armed conflict, armed conflict is divided into two: international armed conflict and non-international armed conflict. The conflict between the SAF and RSF is included in non-international armed conflicts. Based on ACLED data, this armed conflict has a major impact on aspects of life such as: civilians are fatalities; health facilities are not functioning; children who are unable to access education; until logistical access is disrupted. Thus, this conflict requires conflict resolution efforts using the multi-track diplomacy (MTD) method using the second track using non-state actors as mediators to build the game. Through the United Nations which encouraged the United States and Saudi Arabia as mediators who produced the Jeddah declaration.